2008
DOI: 10.1371/journal.ppat.1000054
|View full text |Cite
|
Sign up to set email alerts
|

SARS-Coronavirus Replication/Transcription Complexes Are Membrane-Protected and Need a Host Factor for Activity In Vitro

Abstract: SARS-coronavirus (SARS-CoV) replication and transcription are mediated by a replication/transcription complex (RTC) of which virus-encoded, non-structural proteins (nsps) are the primary constituents. The 16 SARS-CoV nsps are produced by autoprocessing of two large precursor polyproteins. The RTC is believed to be associated with characteristic virus-induced double-membrane structures in the cytoplasm of SARS-CoV-infected cells. To investigate the link between these structures and viral RNA synthesis, and to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
266
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(271 citation statements)
references
References 52 publications
(79 reference statements)
5
266
0
Order By: Relevance
“…The Mpro contained within nsp 5 cleaves nsps 5 through 16. The biological characteristics of many nsps have been previously reported [9,10,[12][13][14][15][16][17]. In addition to nsps 3 and 5, which contain proteases PL2 and Mpro, respectively, nsps 2, 4, and 6 contain hydrophobic residues predicted to play a role in anchoring the RTC to the Golgi.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The Mpro contained within nsp 5 cleaves nsps 5 through 16. The biological characteristics of many nsps have been previously reported [9,10,[12][13][14][15][16][17]. In addition to nsps 3 and 5, which contain proteases PL2 and Mpro, respectively, nsps 2, 4, and 6 contain hydrophobic residues predicted to play a role in anchoring the RTC to the Golgi.…”
Section: Introductionmentioning
confidence: 94%
“…The polyprotein 1ab is translated through a-1 frame-shift translation mechanism that occurs approximately 20-40% of the time [9]. The IBV 1a and 1ab polyproteins are post-translationally cleaved into 15 nonstructural proteins (nsps), nsps 2 through 16 by a papain-like protease (PLP) and the main protease (Mpro), also referred to as the 3C-like protease [10]. IBV does not have an nsp 1 equivalent found in some other coronaviruses.…”
Section: Introductionmentioning
confidence: 99%
“…RNA isolation from infected cells, denaturing agarose gel electrophoresis, detection of 32 P-RNA or viral RNA by hybridization with (strand-) specific probes have been described previously (Albulescu et al, 2014;van Hemert et al, 2008). CHIKV genome copy numbers were determined by internally-controlled TaqMan multiplex RT-qPCR as described (Scholte et al, 2015).…”
Section: Chikv Protein and Rna Analysismentioning
confidence: 99%
“…A previous study by van Hemert et al established a protocol to isolate and monitor the activity SARS-CoV replication complexes in vitro (van Hemert et al, 2008). The study performed by te Velthuis et al used this protocol and showed that zinc-ionophores inhibited the synthesis of RNA by SARS-CoV RdRp.…”
Section: - Cell-based Screens For Sars-cov Antiviralsmentioning
confidence: 99%